The Protective Effect of Gynura procumbens Adventitious Root against Lead Acetate Toxicity in Mice - Dwi Winarni; Ufairanisa Islamatasya; Abdul Hakim Muhsyi; Ahimsa Buena Merpati; Sugiharto Sugiharto; Yosephine Sri Wulan Manuhara (Universitas Gadjah Mada, 2022)
Lead induced oxidative stress contributes to increase the productivity of reactive oxygen species (ROS) and to disrupt the antioxidant balance. Gynura procumbens adventitious root (GPAR) methanol extract contains abundant phenolic and flavonoids compounds as antioxidants and can be used as traditional medicinal plants. The objective of this study is to evaluate the protective effect of GPAR against lead acetate toxicity in mice to haematological parameter, histological of hepatic cells, and activities of antioxidant enzymes. The data obtained from five groups of treatment: P1 (control), P2 (Pb acetate-100 mg/L), P3 (GPAR-100 mg/L + Pb acetate-100 mg/L), P4 (GPAR-200 mg/L + Pb acetate-100 mg/L), P5 (GPAR-300 mg/L + Pb acetate-100 mg/L). The results indicated that administration of methanol extract of GPAR can prevent the decreasing of haematological parameter, maintain the percentage of normal hepatic cells, activities of superoxide dismutase (SOD), and catalase (CAT) due to lead acetate treatment. The effective dose of GPAR extract was 300 mg/L. This study provides that methanol extract of G. procumbens adventitious root exerts protective effects against lead acetate toxicity in mice.